Macao, Qatar and Jordan: A Cross-Country Exploration of Three Countries’ Literacy Enrichment Programs - Cornelia, Uspessy Shuha; Mayuni, Ilza (Elsya : Journal of English Language Studies, 2024)
When assessing a country’s level of education, referring to their Programme for International Student Assessment (PISA) scores can be stated as an overused trend, one that has been criticised as PISA alone is not the most perfect way to judge a country’s readiness. To address this weakness, this study will also refer to the Progress in International Reading Literacy Study (PIRLS), another world-class test that specifically focuses on literacy, yet has been underutilised in reading-related research. This paper is a case study on three countries which have shown different levels of performances. Using PISA and PIRLS reports as the main data and general literature review to supplement the contextual details of the reported results, the analysis focused on how Macao, Qatar and Jordan employ diverse strategies to cultivate and elevate literacy skills among their students. Results show that Macao is a leader in government-led efforts that focused on developing teacher competence, Qatar develops their children’s literacy through collaboration and competition, and Jordan focuses on all language skills in balance (with few programs exclusively concerned on reading competence). The novelty of the findings is its comparison of two international assessments that have a different scope, as PISA offers a holistic view of contextual factors affecting literacy whereas PIRLS covers information that are crucial for understanding early literacy development.